ANALISIS BALANCE SCORECARD DALAM MENILAI KINERJA PADA BPJS KETENAGAKERJAAN KANTOR CABANG NUSA TENGGARA TIMUR - Wilsna Rupilu (Media Mahardhika, 2022)
This study analyzed the balance scorecard as the performance measurement tool, the object of this study is BPJS's Employment of East Nusa Tenggara Branch. The purpose of this study is to determine the performance of the BPJS's Employment of the East Nusa Tenggara Branch by using the balanced scorecard method. This research is a quantitative descriptive study, with the used data sources in the form of primary data (questionnaires) and secondary data, namely the financial position report of 2020. The data analysis technique which used to measure each balance scorecard perspective is by using variables from financial perspective, customer perspective, internal business perspective, and growth development perspectives. The results of this study indicate that the final performance of BPJS's Employment of East Nusa Tenggara Branch Which used the balanced scorecard method with a value of 4.51 or in percent of 90.2% is categorized as very good.